The Effect of particular exercises by using aids to develop the special endurance and the achievement of 400 meters for young athlete - Azad Saleh Aljaf, Naween; Sabah Flayyih, Luay; Noori Taresh, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
View the researchers an introduction to athletics , especially the effectiveness of 400 meters and took the trainers and researchers are looking for better than that can serve the training process and increases the development of the figures, and eliminated the problem low use of special exercises using means of assistance also aims to identify the special exercises using aids in the development of your endurance the effectiveness of ( 4 00 m) for juniors and has assumed the researcher Wen there are significant statistical differences in the endurance of the private and achievement between the pre - test and post for the research sample included a sample search (4) runners for the junior class in the province of Baghdad in the effectiveness of ( 4 00 m) has been used researcher One experimental approach to the sample’s (4), research was conducted cardiac tests on 16/ 6 /2019 17/ 6 /2019 was the formulation of the training curriculum and then it started for a period of 8 weeks after was conducted posteriori tests on 13 / 8 /2019 14 / 8 /2019 were then calculated the results of search variables. The researchers used the statistical bag (SPSS) and through the presentation of results, analysis and discussion of the physical capacities and achievement and discuss the scientific debate to achieve the research hypotheses.